Detrital Garnet and Muscovite in Late Precambrian Sandstone near St. John's, Newfoundland, and their Significance - Papezik, V. S. (Canadian Journal of Earth Sciences, 1973)
The lower member of the Signal Hill Formation of Late Precambrian age, a lithofeldspathic sandstone exposed near St. John's, Newfoundland, contains small but persistent amounts of garnet and muscovite. These minerals are not known to occur in rocks of the Harbour Main Group and the Holyrood granitic pluton of the Avalon Peninsula, previously considered to be the source of the Signal Hill sediments. As paleocurrent studies indicate a northeasterly provenance of the sediment it is suggested that the rock may have been derived from Precambrian gneissic and granitic basement, now covered by the ocean, similar to the Precambrian(?) basement rocks along the western flank of the Avalon Platform.